HUBUNGAN BUNYI, MAKNA, DAN KONTEKS DALAM WACANA PUBLIK: KAJIAN FONETIK DAN SEMANTIK PADA UCAPAN SAHRONI - Muhammad Fakhri Nurfauzan; M. Irwan Jayadi; Ahmad Dardiri; Wati Susiawati (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study analyzes the relationship between sound (intonation, stress, speech tempo), word choice, and contextual framing in shaping public interpretation of Ahmad Sahroni's controversial statement “tolol sedunia” within Indonesian political discourse. The research aims to describe how phonetic features and semantic connotations construct perceived meaning and to formulate more constructive communicative alternatives for sensitive public contexts. A descriptive qualitative approach is used through interpretative linguistic analysis supported by contextual triangulation of speaker identity, sociopolitical situation, and public audience reception. The findings indicate that even when delivered with flat intonation, the prominent stress on a pejorative lexical item reinforces an intentional insulting illocution, amplified by the speaker's authority as a public official amid heightened public distrust toward DPR policies. The study concludes that linguistic form and context interact dynamically to escalate negative social impact, and public communication should prioritize neutral diction and controlled prosody to maintain critical substance while reducing potential communicative conflict.